Labors In The Media: Detik Finance Report On Batam 2015 Labor Strikes - Putri, Astari Fitria; Hartoyo, Nunik Maharani; Saragih, Sahat Sahala Tua (Jurnal Kajian Jurnalisme, 2017)
The impressive economic growth along with its strategic location have made the city of Batam as one of the best economic performer in Indonesia. For years, Batam has attracted foreign investors from countries such as Singapore, China, Korea, Taiwan and Malaysia. However, there was a significant decline in the period of 2013-2015. DetikFinance, an online media, reported and highlighted the fact that frequent labors demonstration and strikes were the main reasons as to why many multinational companies left Batam as well as the FDI decline. Utilizing Norman Fairclough’s model for Critical Discourse Analysis (CDA), this paper finds that DetikFinance’s reports are biased and the labors are painted in a non-favorable fashion: their demands are unreasonable and therefore counterproductive to the economy. In its reporting process as well as in the report texts, DetikFinance also dismisses the fact that during that period, the world economy, including Indonesia, is slowing down. Study reveals that DetikFinance media routines and ideology are in fact serving its own business interests and affect the way they construct and present their reports. In doing so, DetikFinance has violated the very principles of journalism by reporting imbalanced, unverified news and prevent them from serving the public, including business community, a comprehensive explanation of the matter.